Unexpected Heterogeneity of Newly Diagnosed Multiple Myeloma Patients with Plasmacytomas - Stork, Martin; Sevcikova, Sabina; Jelinek, Tomas; Minarik, Jiri; Radocha, Jakub; Pika, Tomas; Pospisilova, Lenka; Spicka, Ivan; Straub, Jan; Pavlicek, Petr; Jungova, Alexandra; Knechtova, Zdenka; et al. (Biomedicines, 2022)
In multiple myeloma (MM), malignant plasma cells infiltrate the bone marrow. In some cases, plasma cells migrate out of the bone marrow creating either para-skeletal plasmacytomas (PS) or infiltrating soft tissues as extramedullary plasmacytomas (EMD). The aim of this study was to define risk groups in newly diagnosed MM (NDMM) patients with PS and EMD plasmacytomas. In total, 523 NDMM patients with PS plasmacytomas and 196 NDMM patients with EMD plasmacytomas were diagnosed in the Czech Republic between 2004 and 2021 using modern imaging methods. Patients’ data were analyzed from the Registry of Monoclonal Gammopathies of the Czech Myeloma Group. In NDMM patients with PS plasmacytomas, we found a subgroup with <5% of bone-marrow plasma cells to have the best prognosis (mPFS: 58.3 months (95% CI: 33.0−NA); mOS: not reached). The subgroup with >5% of bone-marrow plasma cells and ≥3 plasmacytomas had the worst prognosis (mPFS: 19.3 months (95% CI: 13.4−28.8), p < 0.001; mOS: 27.9 months (95% CI: 19.3−67.8), p < 0.001). Our results show association between tumor burden and prognosis of NDMM patients with plasmacytomas. In the case of PS plasmacytomas, NDMM patients with low BM PC infiltration have an excellent prognosis.
Keywords: survival; plasmacytomas; multiple myeloma; risk factors